Expectations of orthodontic treatment among 7–12 year-old children – a cross sectional study - Anne-Maria Aulu; Tuija Pikkusaari; David Rice; Heidi Arponen (Acta Odontologica Scandinavica)
Objective: The primary aim of this study was to investigate participants’ orthodontic treatment expectations and to assess participants’ perceptions of their own orthodontic treatment need. A secondary aim was to compare participants’ self-perceived treatment need to an orthodontist’s opinion.